Developing advanced appliances control system in toilet and bathroom for aged generation: FGD preliminary findings - Hussain, Mohd Rizal; Ahmad, Siti Anom; Rokhani, Fakhrul Zaman; Ashari, Asmidawati; Hassan, Mohd Khair; Haron, Nuzul Azam; Dolah, Mohd Shahrizal; Raja Ahmad Effendi, Raja Ahmad Azmeer; Ramli, Saiful Hasley (Research and Scientific Innovation Society, 2019)
When a person gets old, there are many changes that occur in the aspect of biomechanical features such as bones, joints and muscles which can affect their mobility and strength including reduction in vision and hearing abilities. Thus, this condition will expose them to risk of injuries and accidents. Based on previous studies, toilet and bathroom are identified as the common place where injuries and accidents occur involving older persons. Therefore, in order to create safe and suitable environment for older persons, modifications to products, systems and environments for their daily use should be taken into consideration. Environmental modifications and assistive technology (AT) can compensate for limitations in functional capabilities and thus promoting the well-being and independence of the elderly. In this study, the initial approach is through qualitative methods which was Focus Group Discussion (FGD). Information related to issues and problems, causing factors and suggestions for improvement will be used as an important indicator in the development of relevant systems in this study.